INOVASI BUDIDAYA KANGKUNG CABUT BERBASIS PROGRAM KKN UNTUK MENINGKATKAN KESEJAHTERAAN PETANI DI DESA BAWOMAENAMOLO, KECAMATAN LUAHAGUNDRE MANIAMOLO - Maria Septyani Laia; Samson Wau; Nimar Sidarniwati Hondro; Yoelman Dachi; Arenawati Gaurifa; Brigita Ferni Wati Hondro; Sri Selitiani Duha; Novita Yanti Jagate; Dorotea Hesti Marda Debora Fau; Ruben Saputra Gowasa; Olisman Laowo; Baziduhu Laia (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student engagement aimed at making a tangible contribution to solving community problems in rural areas. Bawomaenamolo Village, located in Luahagundre Maniamolo District, has considerable agricultural potential; however, most farmers still rely on traditional cultivation practices that result in relatively limited yields. One agricultural commodity with strong development potential is water spinach (Ipomoea aquatica), particularly the pull-harvest variety, which is a short-cycle vegetable with high market demand. Through the KKN program, students introduced a simple, efficient, and practical innovation in pull-harvest water spinach cultivation that can be easily adopted by local farmers using home gardens or small paddy fields. The program was implemented through several stages, including observation of local agricultural conditions, socialization with farmers, joint planting practices, and continuous assistance during crop maintenance and harvesting. The results showed that farmers were able to understand the cultivation techniques, apply proper maintenance methods, and harvest the crop within 20–30 days. In addition to providing new agricultural experience for farmers, this innovation has the potential to increase household income through the sale of harvested products in local markets. Therefore, the innovation of pull-harvest water spinach cultivation through the KKN program can serve as an alternative strategy for empowering rural communities in the agricultural sector. This activity not only enhances farmers’ skills but also opens opportunities for sustainable improvements in community welfare when supported by village authorities and implemented consistently.